Characterization of hospital-associated lineages of ampicillin-resistant Enterococcus faecium from clinical cases in dogs and humans - Tremblay, Cindy-Love; Charlebois, Audrey; Masson, Luke; Archambault, Marie (Frontiers in Microbiology, 2013)
Ampicillin-resistant Enterococcus faecium (ARE) has rapidly emerged worldwide and is one of the most important nosocomial pathogens. However, very few reports are available on ARE isolates from canine clinical cases. The objective of this study was to characterize ARE strains of canine clinical origin from a veterinary teaching hospital in Canada and to compare them with human strains. Ten ARE strains from dogs and humans were characterized by multilocus sequence typing (MLST), pulsed field gel electrophoresis (PFGE), antibiotic susceptibility and biofilm activities, presence of rep-families, CRISPR-cas and putative virulence genes. All ARE strains (n = 10) were resistant to ciprofloxacin and lincomycin. Resistances to tetracycline (n = 6), macrolides (n = 6), and to high concentrations of gentamicin, kanamycin and streptomycin (n = 5) were also observed. Canine ARE isolates were found to be susceptible to vancomycin whereas resistance to this antibiotic was observed in human strains. Ampicillin resistance was linked to PBP5 showing mutations at 25 amino acid positions. Fluoroquinolone resistance was attributable to ParC, GyrA, and GyrB mutations. Data demonstrated that all canine ARE were acm (collagen binding protein)-positive and that most harbored the efaAfm gene, encoding for a cell wall adhesin. Biofilm formation was observed in two human strains but not in canine strains. Two to five rep-families were observed per strain but no CRISPR sequences were found. A total of six STs (1, 18, 65, 202, 205, and 803) were found with one belonging to a new ST (ST803). These STs were identical or closely related to human hospital-associated lineages. This report describes for the first time the characterization of canine ARE hospital-associated strains in Canada and also supports the importance of prudent antibiotic use in veterinary medicine to avoid zoonotic spread of canine ARE.